EDUCATION OF SPIRITUALITY OF SENIOR STUDENTS MEANS OF FICTION - N. Kolomiyets (Academy of Cognitive and Natural Sciences, 2002)
Different problems and aspects o f bringing up o f spirit among young generation in studiing Ukrainian literature are opened in this article.